Adaptive trial designs for spinal cord injury clinical trials directed to the central nervous system - Mulcahey, Mary Jane; Jones, Linda A. T.; Rockhold, Frank; Rupp, Rüdiger; Kramer, John L. K.; Kirshblum, Steven; Blight, Andrew; Lammertse, Daniel; Guest, James D.; Steeves, John D. (Spinal cord, 2020)
Narrative review.
Gesehen am 25.09.2025